A highly prevalent SINE mutation in the myostatin (MSTN) gene promoter is associated with low circulating myostatin concentration in Thoroughbred racehorses - O’Hara, Victoria (Sci Rep, 2021)
Horse racing is a popular and financially important industry worldwide and researchers and horse owners are interested in genetic and training influences that maximise athletic performance. An association has been found between the presence of a short interspersed nuclear element (SINE) mutation in the myostatin (MSTN) gene promoter and optimal race distance in Thoroughbred horses. There is previous laboratory evidence that this mutation reduces MSTN expression in a cell culture model and influences skeletal muscle fibre type proportions in horses. Manipulating MSTN expression has been proposed for illicit gene doping in human and equine athletes and already, researchers have generated homozygous and heterozygous MSTN-null horse embryos following CRISPR/Cas9 editing at the equine MSTN locus and nuclear transfer, aiming artificially to enhance performance. To date however, the role of the naturally-occurring equine MSTN SINE mutation in vivo has remained unclear; here we hypothesised that it reduces, but does not ablate circulating myostatin expression. Following validation of an ELISA for detection of myostatin in equine serum and using residual whole blood and serum samples from 176 Thoroughbred racehorses under identical management, horses were genotyped for the SINE mutation by PCR and their serum myostatin concentrations measured. In our population, the proportions of SINE homozygotes, heterozygotes and normal horses were 27%, 46% and 27% respectively. Results indicated that horses that are homozygous for the SINE mutation have detectable, but significantly lower (p < 0.0001) serum myostatin concentrations (226.8 pg/ml; 69.3–895.4 pg/ml; median; minimum–maximum) than heterozygous (766 pg/ml; 64.6–1182 pg/ml) and normal horses (1099 pg/ml; 187.8–1743 pg/ml). Heterozygotes have significantly lower (p < 0.0001) myostatin concentrations than normal horses. Variation in serum myostatin concentrations across horses was not influenced by age or sex. This is the first study to reveal the direct functional effect of a highly prevalent mutation in the equine MSTN gene associated with exercise performance. Determining the reason for variation in expression of myostatin within SINE-genotyped groups might identify additional performance-associated environmental or genetic influences in Thoroughbreds. Understanding the mechanism by which altered myostatin expression influences skeletal muscle fibre type remains to be determined.